2014
DOI: 10.1039/c3ra46925e
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of water oxidation by nanolayered manganese oxide: a step forward

Abstract: New insights into the mechanism of water oxidation by layered Mn oxide are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…3), and another mechanism is related to the attack of an outer-sphere water molecule on an OH group that is coordinated to a high-valent Mn ion in the oxide phase (pathway i in Fig. 3) [47,48]. Interestingly, we observed these two ranges for water oxidation for nano-layered Mn oxides, at least, at pH ¼ 6.3 [48].…”
Section: Mechanism Of Water Oxidation Catalyzed By Layered Mn Oxidesmentioning
confidence: 76%
See 3 more Smart Citations
“…3), and another mechanism is related to the attack of an outer-sphere water molecule on an OH group that is coordinated to a high-valent Mn ion in the oxide phase (pathway i in Fig. 3) [47,48]. Interestingly, we observed these two ranges for water oxidation for nano-layered Mn oxides, at least, at pH ¼ 6.3 [48].…”
Section: Mechanism Of Water Oxidation Catalyzed By Layered Mn Oxidesmentioning
confidence: 76%
“…These results indicate that other scenarios are possible found that such exchanges are too slow [47]. But the question is open if the water exchange in the presence of Ce(IV) or [Ru III (bpy) 3 ] 3þ , not in non-pure water, and under the water-oxidation conditions remains slow or not.…”
Section: Mechanism Of Water Oxidation Catalyzed By Layered Mn Oxidesmentioning
confidence: 92%
See 2 more Smart Citations
“…Among Mn oxides, nanolayered Mn oxides with different organic or inorganic ions between layers are efficient and stable in water oxidation [41]. Inspired by the WOC, layered MnACa oxides were reported as efficient catalyst for water oxidation [42][43][44][45][46][47][48][49][50][51][52][53][54][55]. X-ray absorption spectroscopy (XAS) reveal similarities between layered oxide and MnACa cluster in PSII [42].…”
Section: Introductionmentioning
confidence: 99%